COVID-19-related supply chain disruptions: resilience and vulnerability of micro, small and medium enterprises - Vincent Canwat (Cogent Business & Management, 2024)
The COVID-19 outbreak created a global public health crisis to which governments responded with several measures, including a lockdown on social and economic activities. This study assessed: (1) the supply chain disruptions caused by the lockdown, (2) the supply chain disruption effects on the performance of micro, small and medium enterprises (MSMEs), (3) the resilient strategies (responses) MSMEs adopted to overcome the disruption challenges and (4) how the supply chain disruption affected the performance of MSMEs and how their responses varied across different MSME and supply chain characteristics. Using descriptive statistics and t-tests, the study found that the COVID-19 lockdown reduced the quantity, quality and order lead time of goods supplied. It also halted the supply of some other goods. Disruptions in the supply chain affected MSMEs' performance by reducing quantity, quality, variety of goods stocked, reliability to customers and customer base. MSMEs responded to the supply chain disruptions by changing their purchase arrangement, reducing the number of employees, increasing product prices, closing businesses temporarily and diversifying businesses supplying essential products such as foods and sanitary materials. Performance and responses of MSMEs varied depending on the age, size, location, registration status, product and industry.
Keywords: 650; COViD-19; supply-chain-disruption; MsMe-vulnerability; MsMe-resilience